Major Changes in Extreme Dust Events Dynamics Over the Arabian Peninsula During 2003–2017 Driven by Atmospheric Conditions. Issue 24 (21st December 2020) - Gandham, Harikishan; Dasari, Hari Prasad; Langodan, Sabique; Karumuri, Rama Krishna; Hoteit, Ibrahim
Abstract: Mineral dust emitted from the arid regions of the Arabian Peninsula (AP), in particular Kingdom of Saudi Arabia (KSA), is an important contributor to the northern hemispheric aerosol loading. Dust events over AP are frequent and persistent throughout the year, with a peak in occurrence and intensity between March and August. This study examines the variability of dust events that occurred over AP during 2003–2017 using long‐term dust optical depth retrieved from MODIS satellite measurements. Dust profiles were derived from CALIOP satellite measurements to assess the vertical distributions of the dust events. Our analysis suggests that the formation of extreme dust events is primarily associated with strong high‐pressure systems that occur over AP. Northerly Shamal winds transport dust aerosols from surrounding arid regions to the AP, amplifying the dust aerosol loading across the country. CALIOP dust profiles show that the dust aerosols reach up to 4 km height above sea level, with peak concentrations at an altitude around 1.5 km. Dry deposition of dust is the dominant removal process over the Arabian Gulf, and wet deposition of dust is the dominant removal process over the Red Sea. A total of 49 extreme dust events occurred during the period between 2003 and 2017, over a combined total of 207 days. We observe a significant increase in the frequency of dust events between 2007 and 2012, peaking in 2012, followed by a marked decrease in the following years. We attribute this sudden decline in dust activity after 2012 to enhanced winter rainfall, after noticing increased soil moisture and vegetation coverage during the dust seasons that followed wetter winters. A strengthened Red Sea trough in the middle and the upper altitudes produced favorable conditions for strong moisture convergence and increased rainfall over AP, which may have dampened dust activity during 2013–2017. Key Points: Dust optical properties extracted from MODIS and CALIOP Formation stages and trends of extreme dust events discussed Recent decline in the dust events explained